Analisis Strategi Pemasaran Produk, Promosi, dan Fasilitas Fisik Jasmine Cakery - Rejeki, Marsudi Endang Sri; Baitirahman , Anisa Nur (Universitas Ahmad Dahlan, 2024)
The food business was growing very rapidly and is in great demand by community in addition to its relentless needs. The increasing number of businesses engaged in food will result in competition for market share and consumers. Therefore, it is necessary to have a marketing strategy to maintain and develop its business. This study aims to determine the implementation of the marketing strategy of Jasmine Cakery Products, Promotions, and Physical Facilities. The method used descriptive qualitative research conducting interview, observation, and documentation. Sources of data obtained as primary data include marketing managers, outlite leaders and secondary data obtained from literature, books, articles, news and others. The data analysis performed data reduction, as well as data triangulation for validation. The results show Jasmine Cakery had implemented a marketing strategy of products, promotions, and physical facilities. The products produced are premium, hygienic, and halal-certified products, there are ± 200 product variants with best-selling products, namely choco bun, banana bread, and chocolate cake as well as Spotify cake as a signature product. The promotion used by Jasmine Cakery is to use social media such as Instagram, tiktok, and use the services of an influencer. To establish customer loyalty, Jasmine Cakery launched a membership application, namely